2022
DOI: 10.7717/peerj.12849
|View full text |Cite
|
Sign up to set email alerts
|

Adult bonobos show no prosociality in both prosocial choice task and group service paradigm

Abstract: Previous studies reported contrasting conclusions concerning bonobo prosociality, which are likely due to differences in the experimental design, the social dynamics among subjects and characteristics of the subjects themselves. Two hypotheses have been proposed to explain the occurrence of prosociality in animals: the cooperative breeding hypothesis and the self-domestication hypothesis. While the former predicts low levels of prosociality in bonobos because they are non-cooperative breeders, the latter predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 107 publications
0
19
1
Order By: Relevance
“…We discussed how kin favoritism and dyadic social tolerance in a despotic society could drive prosocial motivations. Although we did not find the age difference of the individuals to influence prosociality significantly, participation of a relatively large number of juveniles can not be neglected; for instance, due to their higher social tolerance, bonobo sub-adults have been shown to be more prosocial than adults (32). Nonetheless, prosociality was not restricted to juveniles, and therefore, we speculate on the role of complex socio-ecological and living conditions in facilitating individual prosocial motivations.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…We discussed how kin favoritism and dyadic social tolerance in a despotic society could drive prosocial motivations. Although we did not find the age difference of the individuals to influence prosociality significantly, participation of a relatively large number of juveniles can not be neglected; for instance, due to their higher social tolerance, bonobo sub-adults have been shown to be more prosocial than adults (32). Nonetheless, prosociality was not restricted to juveniles, and therefore, we speculate on the role of complex socio-ecological and living conditions in facilitating individual prosocial motivations.…”
Section: Discussioncontrasting
confidence: 58%
“…The fact that active solicitation and the presence of individuals being potential receivers did not necessarily elicit prosociality also indicates its proactive nature. For instance, active solicitation, begging or signal prompting has been argued to be a stimulus enhancement mechanism of rather "reactive" prosociality (19,31,32). In contrast, some studies even found a negative role of signal prompting on prosociality (34)(35)(36).…”
Section: Genuine Prosocial Intentmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of IA research in great apes has focused on chimpanzees, bonobos make a very interesting study species to investigate advantageous and disadvantageous IA. Bonobos are often said to be very peaceful, tolerant, prosocial, and empathic (Furuichi, 2011; Hare et al, 2007; Maclean, 2016; Parish et al, 2000 but see Cronin et al, 2015; Jaeggi et al, 2010; Stevens et al, 2008; Verspeek et al, 2022), and have been shown to cooperate in experimental food retrieval studies in the lab (Hare et al, 2007; Nolte & Call, 2021). Under the cooperation hypothesis it could be expected that IA may be equally expressed in bonobos compared to chimpanzees.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to chimpanzees, bonobos are a male‐philopatric species, meaning that males stay in their natal groups, while females migrate to other communities when they reach maturity (Hashimoto et al, 2008; Kano, 1992). Unlike chimpanzees however, female bonobos engage in strong cooperative bonds among each other as well as with their adult sons (Hohmann & Fruth, 2002; Parish, 1994; Stevens et al, 2006; Surbeck & Hohmann, 2008), resulting in high value relationships between females, but not between males (Stevens et al, 2015; Verspeek et al, 2022). Males on the other hand do not form strong bonds among each other and only rarely engage in cooperative interactions (Hohmann & Fruth, 2002; Ihobe & Furuichi, 1994; Kano, 1992; Surbeck et al, 2017), and show low value relationships (Stevens et al, 2015; Verspeek et al, 2022).…”
Section: Introductionmentioning
confidence: 99%